RELATIONSHIP BLOOD TRIGLYCERIDE LEVELS WITH ACNE VULGARIS IN YOUNG ADULTS - Febianingrum, Adhani; Anggowarsito, Jose L.; Tahalele, Paul L. (JOURNAL OF WIDYA MEDIKA JUNIOR, 2024)
Introduction: Acne vulgaris (AV) is a chronic inflammation of the pilosebaceous follicles. The four main pathologies underlying the occurrence of acne vulgaris are follicular epidermal hyperproliferation, increased sebum production, colonization of Propionibacterium acnes and inflammatory processes. Triglycerides are a component of sebum which plays an important role in the inflammatory process.Objective: to determine the relationship between triglyceride levels in the blood and acne vulgaris in young adults.Method : this research is analytic. The research design used was cross sectional. The population of this study were all patients who came to the clinic. The sample in this study used an accidental sampling technique.Results: The study showed that the characteristics of the respondents based on the Chi-Square test for the relationship between triglyceride levels and the incidence of Acne vulgaris showed that there was a statistically significant relationship between triglyceride levels and the incidence of Acne vulgaris.Conclusion: There is a relationship between triglyceride levels in the blood and the incidence of acne vulgaris in young adults.